The ACIRA Registry: A Regional Tool to Improve the Healthcare Pathway for Patients Undergoing Percutaneous Coronary Interventions and Coronary Angiographies in the French Aquitaine Region. Issue 1 (March 2020) - Lesaine, Emilie; Saillour-Glenisson, Florence; Leymarie, Jean-Louis; Jamet, Isabelle; Fernandez, Laura; Perez, Corinne; Legrand, Jean-Pierre; Salmi, Louis-Rachid; Coste, Pierre
Abstract : Background: In France, there is a lack of information about practices and pathways of coronary angiographies and percutaneous coronary interventions (PCI). We present the design and the first results of the ACIRA registry, the goal of which is to answer questions about quality, security, appropriateness, efficiency of, and access to interventional cardiology (IC) healthcare pathway in the French Aquitaine region. Methods: The ACIRA registry is an on-going, multicenter, prospective, exhaustive, scalable, and nominative cohort study of patients who undergo coronary angiographies or percutaneous coronary intervention in any of the catheterization laboratories. The data related to hospitalizations and procedures are directly extracted from hospital information systems. In-hospital mortality, readmissions, and cardiovascular morbidity are collected from the French hospital medical information system database. An identity management system has been implemented to create the patient health care pathway. Results: From January 1, 2012, to June 30, 2018, 147, 136 procedures performed on 106, 005 patients have been included in the ACIRA registry. Conclusions: ACIRA has shown its ability to study the patient IC healthcare pathway, up to 1 year after the procedure. Nominative data enable the linkage between clinical and medico-administrative databases and possible supplementary data collection. The use of existing databases allowed us to limit patients lost to follow-up, prevent the double entry of data, improve data quality, and reduce the operating costs. The prospect of linkage with the French National Health Data System may offer promising opportunities for future medical research projects and for developing collaboration and benchmarking with other IC registries abroad.